The Effect of Board Gender Diversity, Board Size, and Capital Structure on Firm Performance Moderated by Institutional Ownership - Wirawan, Jennifer; Budidarma, I Gusti Agung Musa (Dinasti Publisher, 2024)
The aim of this study was to examine the effect of board gender diversity, board size, and capital structure on firm performance in energy sector companies listed on the Indonesian Stock Exchange for the 2021–2023 period, which was moderated by institutional ownership. This study employed a purposive sampling technique, with a total sample size of 93 companies’ data. The data were analyzed using the SPSS program, specifically through moderated regression analysis. The results showed that board gender diversity and capital structure had no effect on firm performance, whereas board size had a negative effect. In addition, institutional ownership moderated the effect of board size and capital structure on firm performance; on the contrary, it did not moderate the effect of board gender diversity on firm performance.